Hard Power: The Stone Statues of Ammon - Schmidt, Katharina (The Biblical archaeology review, 2023)
Ammon was the northernmost of the Transjordanian kingdoms, formed at the beginning of the tenth century BCE in the highlands east of the Jordan Valley. To the south lay Ammon’s sister kingdoms, Moab and Edom. Far to the north was the kingdom of Aram-Damascus. Israel and Judah lay to the west of the Jordan Valley […]